(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
self- medication is described as obtaining and consuming one (or) more drugs or medications without the advice of physician either for diagnosis, prescription (or) surveillance of the treatment. The main aim of research is to estimate the prevalence of self- medication of analgesics among hospitalized patients along with causes of illness and symptoms that lead to self-medication. The study was conducted in a tertiary care hospital .a total sample of 226 subjects was investigated by using a self- questionnaire form .based on findings the prevalence of irrational use of analgesics are about 65% of females (n=144) and 37% of males (n=82).self -medication was more prevalent among age group above 45years in which female are in greater use. self -medication is most commonly used in participants who are having joint pains (51%), muscle pains (29%), head ache (28%), back pain (21%),.among them 21.26% are having confidence on knowledge about medication. During self -medication with analgesics patients stop taking medicine after symptoms disappeared(62.30%),a few days after recovery (13.11%),after completion of course (18.85%),after consulting doctor /pharmacist (4.92%).over use of analgesics causes kidney and heart problems .72.72%does not know causes and uses analgesics frequently of the total participants only 43.52%are in aware that pharmacist will explain about medication usage. This research is carried out mainly in the context to raise awareness of the dangers of self -medication of analgesics. There is need to aware public that pharmacist can explain about drugs, their side effects.